A Proposed Model for Inventory Management to Minimize the Rate of Raw Materials Tied up of Textile Industry with Lean Engineering Tools - Aguilar Paz, Aryanna Frances (2023)
This research focuses on improving the stock rotation of the raw materials warehouse of a sheep wool yarn production plant. The objective is to reduce excessive operating costs, the misuse of resources and improve the distribution of materials in the warehouse. This article develops an innovative solution, where the 7S, Poka-yoke, Slotting, and Kardex tools were used to improve the deficiencies in the inventory management systems and the storage conditions of the materials, as well as errors in the stock register. The case study is divided into four stages analysis of the problems and causes, improvement of inventory management activities and tools, evaluation of the impacts generated, and validation of the proposed model. This was carried out in the simulation software Arena, where an increase from 0.83 to 2.4 in raw material turnover, reduced errors in inventory control, and an improvement in the efficiency of inventory management were observed. This case study provides a foundation for other lines of investigation and the model's use by businesses with comparable traits.